Chiropractic Treatments and Scoliosis-specific Exercise Therapy as An Alternative to Bracing for Adolescent Idiopathic Scoliosis: A Narrative Review - Kwok, Ronald; Yau, Kristy Hoi Ying; Leung, Benson Kai Yin; Cheong, Benjamin Kah Chun (British Journal of Healthcare and Medical Research, 2022)
This narrative review aimed to investigate the efficacy of chiropractic treatments and scoliosis-specific exercise (SSE) for adolescent idiopathic scoliosis (AIS) as an alternative treatment for bracing. We searched the PubMed, Index to Chiropractic Literature, Spine Journal, BioMed Central, Google Scholar, and Research Gate databases to identify the most current reviews (2018-2021). A total of 156 papers were identified, of which six were finally included in the analysis, after excluding 150 that were either duplicate studies or failed to meet the inclusion criteria. However, one paper was included despite failure to meet the inclusion criteria because we believed the findings were significant, and hence, it was worth reviewing. All the reviewed papers reported the benefits of exercise and chiropractic as part of AIS management. Only one study showed that SSE alone slows curve progression, whereas the other six papers (four papers investigating chiropractic intervention alone and two investigating SSE alone) showed significant curve reduction after analyzing the X-ray findings. The other outcomes included increased flexibility, greater trunk rotation angle, and improved quality of life. The quality of the evidence in these studies ranged from very low to moderate. Despite the lack of high-quality research, the evidence reviewed illustrates the benefits of chiropractic treatments and Schroth therapy for AIS patients. The findings also suggest that SSEs and chiropractic manipulations can be used either alone or in combination as an alternative to bracing.